Frequency of migraine among patients followed at the Epilepsy Clinic of the Hospital das Clinicas, Universidade Federal de Minas Gerais - Faleiros, Bruno Engler; Sousa-Pereira, Sílvio Roberto de; Coelho, Bernardo Cardoso Pinto; Lara, Marilis Tissot; Portela, Eduardo Jardel; Teixeira, Antônio Lúcio (Headache Medicine, 2010)
The relationship between migraine and epilepsy is well known for many years. Both conditions are chronic neurologic disorders, occur in paroxistic attacks and present a series of clinical features in common. The objective of the present study was to determine the frequency of migraine among epileptic patients seen in the Epilepsy Clinic of University Hospital of the Federal University of Minas Gerais, Belo Horizonte, Brazil. This is a transversal descriptive study based on the analysis of 554 medical charts from patients evaluated consecutively in one year period. The diagnosis of migraine was recorded in 3.1% of the medical charts. Only gender differed between epileptic patients with and without migraine. The frequency of migraine found in this study is lower than the reported in the literature. Possibly this finding result from the methodology used and/or other factors such as the relative negligence of headache complaint and the use of anti-epileptic drugs, such as valproic acid or topiramate, also effective for migraine prophylaxis. It is relevant to actively search for the diagnosis of migraine in epileptic patients in order to provide them better clinical treatment and quality of life.